Pengaruh Label Halal, Harga, dan Kualitas Produk terhadap Keputusan Pembelian Produk Fast Moving Consumer Goods (FMCG): - Safa Haliza; Riyan Pradesyah (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to detect the influence of halal labels, prices and product quality on purchasing decisions for Fast Moving Consumer Goods (FMCG) products in the community in Sunggal Kanan village. The independent variables in this study were halal label (X1), price (X2) and product quality (X3). The dependent variable in this study is the purchase decision towards the purchase of FMCG products. The sample used in this study was 50 respondents from the FMCG consumer population in Sunggal Kanan village. In this study, the method used was the primary data collection method or directly using questionnaires. This study conducted statistical tests using PLS-based Structural Equation Modelling. Validity tests using factor loading values, and reliability tests using Cronbach's Alpha, Composite Reliability and Average Variance Extracted (AVE) values. From the results of this analysis research states that the halal label variable has a significant impact and has a positive effect on FMCG product purchasing decisions. Meanwhile, the Price and Product Quality variables do not have a significant impact on FMCG product purchasing decisions. Keywords: Halal Label, Price, Product Quality, Purchasing Decision